OPINION DE LA POPULATION SUR APPORT DE L’UNIVERSITE A LA COMMUNAUTE DANS LA CITE D’IKELA - MBULA , Mathieu LOFULA; NDJATE, Jean Mocha LOKONGO (IJRDO - Journal of Social Science and Humanities Research, 2022)
The major concern of our research stems from an observation that, since 2008, the Minister of Higher and University Education has authorized the establishment of a university in the city of Ikela in order to give access to anyone having the desire to study. The height is to note that soon 14 years of existence, this transformation is not so obvious. It is in this perspective that we conducted our study in order to feel the reality.